PROSPECTS FOR THE DEVELOPMENT OF BIODIESEL PRODUCTION IN UKRAINE WITH CONSIDERATION OF SOCIO-ECONOMIC AND ENVIRONMENTAL EFFICIENCY - Ihor Kupchuk; Tatiana Yemchyk; Yaroslav Gontaruk (Baltic Journal of Economic Studies)
The article's objective is twofold: firstly, to explore the prospects for biodiesel production, and secondly, to develop a universal methodology for evaluating its efficiency. In doing so, the social, economic and environmental aspects of Ukraine will be given full consideration. Methodology. The research was conducted utilising the following methodologies: a cause-and-effect analysis was employed to ascertain the socio-economic and ecological efficiency of biodiesel production; statistical and economic methods were implemented for the retrieval, processing, and analysis of statistical data; and a logical generalization was employed for the formulation of conclusions. Graphical representation was employed for the creation of a diagram illustrating an algorithm for biodiesel and by-product production within an energy co-operative. The study examined the volumes of rapeseed production and highlighted the impracticality of fully exporting this crop and its oil products. The study identified leading biodiesel production technologies and substantiated their economic feasibility. The findings indicate that the organisation of biodiesel production in the form of energy co-operatives has the potential to fully meet the agricultural sector's demand for fuel and to promote the development of related industries, including animal husbandry. The research evaluates the economic feasibility, environmental impacts, and social aspects of biodiesel production. Utilising a data-driven approach, encompassing a comprehensive analysis of oilseed crop production, production costs, and market prices, a model was meticulously developed to assess socio-economic and ecological efficiency. The study identified the key advantages and barriers to the industry's development, and recommended state policy measures to stimulate biodiesel production. The need to create co-operatives to unite agricultural producers for the joint production of biodiesel is identified. The study highlights the need for scientific research to improve biodiesel production technologies, in particular by increasing the oil content of certain rapeseed varieties. The analysis shows that with rapeseed costing 14,160 UAH/t (purchase price from agricultural enterprises), transport costs of 40 UAH/t /km and processing costs of 900 UAH/t, the total production cost will be 16,260 UAH/t. The planned biodiesel production of 450 kg per tonne requires an additional investment of 2,050 UAH. By-product revenues are estimated at 5,900 UAH, resulting in biodiesel production costs of 33 UAH per kg or 28.44 UAH per litre. The research findings can be used to develop effective strategies for promoting bioenergy in Ukraine. Practical implications. The following practical implications of biodiesel production in Ukraine can be deduced from the conducted study: enhanced energy independence, promotion of agricultural development by means of the processing of oilseed crops, creation of new employment opportunities in rural areas, reduction of greenhouse gas emissions, increase in budget revenues, encouragement of the development of new technologies in the bioenergy sector, and establishment of scientific schools with a focus on research in bioenergy. Value / Originality. The study's originality lies in the development of an algorithm for the operation of energy co-operatives, with the objective of meeting the needs of agricultural enterprises for biodiesel and concentrated feeds. The study also includes the development of a universal methodology for assessing the socio-economic and ecological efficiency of biodiesel production.